Functional molecules regulated and intercalated nickel-cobalt LDH nano-sheets on carbon fiber cloths as an advanced free-standing electrode for high-performance asymmetric supercapacitors. (20th October 2019) - Lan, Yeqian; Li, Minyu; Fan, Wei; Deng, Qiang; Zeng, Zheling; Wang, Jun; Deng, Shuguang
Abstract: With the aim to enhance the performance of pseudo-capacitor electrode materials, a novel free-standing hybrid electrode through integrating vertically aligned sodium dodecyl benzene sulfonate (SDBS) intercalated NiCo LDH nanosheets and carbon fiber cloth (CFC) was synthesized via a one-step hydrothermal method. The SDBS could serve as NiCo LDH growth regulator and interlayer distance expander. Upon SDBS intercalation the LDH interlayer space increase from 0.79 nm to 1.52 nm, the enlarged interspace could significantly facilitate the ion transportation and boost the specific electrochemical performance. Moreover, the as-prepared NiCo-SDBS-LDH@CFC hybrid material delivers an excellent specific capacity of 748.2 C g −1 at 0.5 A g −1 and outstanding rate capacity of 78.9% at 10 A g −1 . Contributed by the delicately engineered electrodes, a high performance of asymmetric supercapacitor (ASC) is constructed, which exhibited a high energy density of 70.94 Wh kg −1 at a power density of 400 W kg −1, the energy density can still remain as high as 59.11 Wh kg −1 at a high power density of 8000 W kg −1 . Furthermore, the ACS cell manifests a long lifespan of 89.96% capacitance retention at 10 A g −1 even after 10000 cycles. This work not only demonstrates an attractive strategy for rational design and modification of LDH-based electrodes, but also provides superior nanostructured free-standing electrodes for high energy density supercapacitors. Graphical abstract: Image 1